DOES SMOKING CAUSE ORAL CANDIDA COLONIES GROWTH? - Sarah Mersil; Naifadiniaulia Lailiqonita (Universitas prof. Dr. Moestopo (Beragama), 2021)
Smoking is associated with a variety of changes in the oral cavity. Smoking has effects on oral commensal microorganisms, mainly Candida, which causes oral thrush. This infection disease is caused by oral candida colonies growth. How smoking affects oral candida colonies growth is still controversial. The aim of this study is to prove smoking causes oral candida colonies growth. This study is an observational analytic study. The sample of this study consisted of smokers and nonsmokers; oral candida is taken in the oral cavity using swab method. Candida is identified using sabouraud’s dextrose agar (SDA) and incubated at 37⁰C for 24-48 hours. We are asking how to maintain oral hygiene and about oral complaints that carried out using a questionnaire. Oral candidal colonization are both higher in the smokers compared to the nonsmokers; however, the difference was not statistically significant. The p-value is 0.820 (p value> 0.05). Smoking does not cause oral candida colonies growth. Have a good habits of maintaining oral health may control oral candida colonies growth.